Competitive Analysis of OSI and TCP/IP Models: Architecture and Protocols in Networking Systems - Janighorban, Amirarshia; Kaveh, Navid (Global journal of Business and Integral Security, 2025)
To ensure optimal performance and system compatibility, it is essential to understand the theoretical basis of data transfer in computing and networking. Both models help in understanding how communication is divided into multiple layers with each layer having specific functions and responsibilities. The OSI model consists of seven layers, offering a structured approach. The TCP/IP model has four layers and emphasizes practical application-layer services and data transfer quality. Both models focus on consistent, reliable communication for interoperability across various network environments. This study compares the functionality and responsibilities across all layers in the OSI and TCP/IP models. The study covers process encapsulation and decapsulation, session management, reliable data transport, and lifecycle processes. Key Words: OSI Model, TCP/IP Model, protocols, Encapsulation, Decapsulation, Session Management, and Ensuring Reliability.